Medical students' perceptions and expectations regarding digital health education and training: A qualitative study. (May 2022) - Edirippulige, Sisira; Gong, Sophie; Hathurusinghe, Malshi; Jhetam, Sarah; Kirk, Jasmine; Lao, Henry; Leikvold, Annalise; Ruelcke, Jayde; Yau, Nim Chi; Zhang, Qichen; Armfield, Nigel; Senanayake, Buddhika; et al.
Introduction: Digital health – the convergence of digital technologies within health and health care to enhance the efficiency of health-care delivery – is fast becoming an integral part of routine medical practice. The integration of digital health into traditional practice brings significant changes. Logic dictates that for medical practitioners to operate in this new digitally enabled environment, they require specific knowledge, skills and competencies relating to digital health. However, very few medical programmes in Australia and globally include digital health within their regular curriculum. This pilot study aimed to explore medical students' perceptions and expectations of digital health education and training (ET). Methods: An online survey and focus groups were used to collect information about medical students' perceptions and expectations relating to digital health and ET relating to this field within the medical programme at the University of Queensland. Sixty-three students took part in the survey, and 17 students were involved in four focus groups. Results: Most participants had no formal ET in digital health. Most participants ( n  = 43; 68%) expressed a willingness to learn about digital health as part of their medical programme. Discussion: Primarily, knowledge- and practice-related factors have motivated students to learn about digital health. The analysis of focus group data identified two superordinate themes: (a) drivers of digital health ET and (b) expectations relating to digital health ET. Students agreed that digital health is a relevant field for their future practice that should be taught as part of their regular curriculum.